The silica and silicon luminescence induced by fast hydrogen ions - Kalantaryan, O.V.; Kononenko, S.I.; Muratov, V.I. (Вопросы атомной науки и техники, 2000)
The results of silica and silicon luminescence induced by hydrogen ions bombardment with energy 0.2 ÷ 0,45 MeV and 0.8 ÷ 2.4 MeV were presented in this paper. It was obtained that the ionluminescence spectra of SiO₂ were changed under hydrogen ions bombardment essentially. The relation between light intensity and implantation dose was determined. The silicon spectra were measured in the near ultraviolet and visible regions of wavelength. The spectra consist of three wide bands. The band with maximum at 326 - 328 nm was not observed earlier. The mechanisms of generation of these bands are discussed. The possibilities to discover oxide layer formed by the natural way on a silicon surface are shown. The novel method for control of proton dose in quartz was proposed.